The Effect of Tax Planning, Capital Intensity and Earning Power On Earning Management with Institutional Ownership As A Moderating Variable - Maria Djojo, Vania; Dwi Astuti, Christina (Devotion : Journal of Research and Community Service, 2023)
The purpose of this research is to examine the factors that influence earnings management in consumer goods manufacturing companies listed on the Indonesia Stock Exchange. These factors are Tax Planning, Capital Intensity, Earning Power and Institutional Ownership as moderating variables. The population used in this research is all consumer goods industry companies listed on the Indonesia Stock Exchange from 2018 to 2021. The sample in this study is 116 data that match the criteria. Samples were selected using purposive sampling method. The results of this study indicate that tax planning has a positive effect on earnings management, capital intensity has a negative effect on earnings management and institutional ownership weakens the effect of tax planning on earnings management. Meanwhile, the variables of earning power, financial leverage and company age have no effect on earnings management and institutional ownership cannot weaken the effect of capital intensity and earning power on earnings management